Testing the peak running speed in analytical and contextual-based scenarios: Applied research in young adult soccer players - Clemente, F. M.; Akyildiz, Z.; Garrett, J.; Beato, M.; Yildiz, M.; Birlik, S.; Moran, J. (Journal of Sports Sciences, 2023)
The primary aim was to compare the peak running speed (PRS) attained in the 40-m linear sprint test, in an analytical-based soccer drill, in the 5-0-5 test, and a training match scenario. The secondary aim of the study was to evaluate the differences between the three assessment sessions and identify how the tests can vary from session to session. Additionally, we aimed to investigate the within-test variability to understand how consistent the performance is within each test format across the different sessions. Forty male under-19 players competing at the national level participated in this study. A training session was observed for each of the three study weeks in which the following tests/scenarios were monitored using a GPS. The 40-m linear sprint test and the analytical-based soccer drill presented the smallest within-subject coefficients of variation between the sessions. A large correlation (r = 0.742) was found between the PRS during the 40-m linear sprint test and the analytical-based soccer drill. The 40-m linear sprint test was the best method of those examined for measuring PRS. The analytical drill provides a reliable method for measuring PRS, although it differs from the 40-metre linear sprint test.